Evaluación De Capacidades De Innovación En Pymes Del Sector Hotelero De La Ciudad De Villavicencio. - Lopez Gavirrian, Eyner Ediliar; Henao Mattar, Aidy Nataly (Universidad Antonio Nariño, 2023)
The main objective of this res earch was; Evaluate the innovation capabilities of a sample of Pymes from the hotel sector in the city of Villavicencio. For its scope, the research started from the following steps: the first was the selection of the sample of Pymes from the hotel sector of the city of Villavicencio whose innovation capacities were evaluated, the second, the application of the instrument was carried out to the survey of the information previously selected, the third, was the analysis of the results obtained in the course o f the application of the instrument in the sample of Pymes. The methodology used was the quantitative method since it revealed statistical data in some cases already studied, it should be noted that the tool used was the survey, applied to owners, managers administrative staff or receptionists of the thirtyand/or administrators, three hotels Mipymes of the city of Villavicencio Meta. It is there where it was possible to define that 55% of the hotels do fulfill a position responsible for leading the innovat ion actions in the company, also 60% of the hotels have defined an innovation strategy and 55% of the hotels have with adequate technology to support the creation of new products/goods/services.